Radiological imaging in pediatric rheumatic diseases - Matuszewska, Genowefa (International Scientific Literature, Inc., 2014)
Radiological imaging plays a fundamental role in the diagnosis and monitoring of rheumatic diseases. The basic method of imaging is a classic X-ray picture, which for many years has been used as a single method for the recognition and evaluation of the effects of disease management. In today’s modern day treatment of rheumatic diseases, ultrasonography and magnetic resonance are more commonly performed for early detection of inflammatory changes in the region of soft tissue, subchondral bone and bone marrow. In spite of their usefulness and fundamental role in the diagnosis, X-ray still remains an essential tool in the diagnosis of rheumatoid arthritis in children and is complementary to today’s methods of imaging diagnostics. In clinical practice, X-ray imaging is still an important examination performed not only to recognize the disorders, but also to provide a differential diagnosis. It helps estimate disease progression and is used to monitor the effects of treatment and the development of possible complications. Differential diagnosis of rheumatic diseases is performed on the basis of localization and type of radiographic changes. The surrounding periarticular soft tissues, bone structures, joint space, with special attention to articular bone surfaces and epiphyses, are analyzed. The aim of this work is to describe characteristic inflammatory changes present on X-ray imaging typical for the most commonly diagnosed rheumatic diseases in children, such as juvenile idiopathic arthritis, systemic lupus erythematosus, systemic scleroderma, mixed connective tissue disease, juvenile dermatomyositis, juvenile spondyloarthropathy and systemic vascular disease.